تطبيق أنشطة التحضرية في المدرسة الجزائرية دراسة ميدانية في ولاية الأغواط - سهيلة حفيطمي; بومجان نجلة; محمد صخري (My University, 2022)
The study aims to apply preparatory education activities in Algerian educational institutions, by knowing the extent of their application in schools. The importance of our study is manifested in determining the nature of students’ education in the preparatory department, and showing the shortcomings that they suffer from. For this purpose, we followed the descriptive analytical approach, relying on the questionnaire as a main tool for collecting information. And evaluated quantitatively in percentages. At the end of our study, we concluded that the preparatory education activities in the (social/emotional) and (mental/cognitive) domains are applied at a high level in schools, while the preparatory education activities in the sensory/motor domain are applied at a low level, and therefore we can say that the preparatory education activities are applied at a low level. high in schools. assessment, preparatory education, school